Geology and Wine 2. A geological foundation for terroirs and potential sub-appellations of Niagara Peninsula wines, Ontario, Canada - Haynes, Simon (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2000)
Summary All of the vineyards in Niagara are planted on soils derived from a variety of Late Pleistocene to Early Holocene, subglacial and proglacial sediments. These were deposited during a series of Late Wisconsinan continental ice advances andre treats, on a landscape that had been carved into the Paleozoic bedrock by this and earlier Quaternary glaciations to form the several landforms that exist above, on,and below the cuesta of the Niagara Escarpment. This paper proposes that the existing delineation of grape viticultural areas, by climate zone, be considerably modified by the recognition that it is the significant differences in the geology that control distinction of terroirs and sub-appellations based on variation of land-form physiography, soil types, and groundwater flow conditions. From considerations of these geological and climatic differences, in combination with wine profiles distinguished by J-L. Groux, winemaker at Hillebr and Estates, the Niagara Peninsula Designated Viticultural Area can be divided into at least eight sub-appellations.